DIDACTIC POSSIBILITIES OF TEACHING PHYSICS TO ACADEMIC LYCEUM STUDENTS BASED ON THE STEM APPROACH (European Journal of Interdisciplinary Research and Development, 2025)
This study analyzes the didactic possibilities of teaching physics to academic lyceum students based on the STEM approach. It highlights ways to develop students’ scientific thinking and competencies through integrated teaching, practical tasks, and problem-based situations.